TAMAN BUDAYA RAJA ALI HAJI DENGAN PENDEKATAN KEARIFAN LOKAL DI TANJUNGPINANG - Niken Arimbi; Rachmadi Nugroho; Suparno Suparno (ARSITEKTURA, 2017)
Abstract: Malayan culture given a lot of culture heritage, even it is an object or not. Pass through culture creation, the point of view of a region could be known. The downfall of Majapahit kingdom caused the development of islamic kingdom in the malayan territory , ingclude in the Kesultanan Riau Lingga. The efforts that have been done by the local goverment is pary seriousness to do conservation of local culture. But all of these efforts has not given any real result yet. To embed the identity of the culture city, the goverment of Tanjungpinang announced officially a zone that is called Taman Budaya Raja Ali Haji is based on the discerment aspect of local malayan culture that has been formed that origin citizen or new comers indirectly affects by the usual and culture of Malayan. Taman Budaya Raja Ali Haji came out from thoughts about an effort in Tanjungpinang. The discernment of Malayan local culture became the strength of culture that the origin citizen and new comers have who lived at Malayan zone. Keywords:  Taman Budaya Raja Ali Haji, malayan culture, local wisdom